A refractory material based on polycrystalline alumina fiber and its preparation method

By uniformly mixing polycrystalline alumina fibers with composite binders and sintering at programmed temperatures, a refractory material with excellent high-temperature stability and strength was prepared, solving the problems of thermal shock resistance and weak interfacial bonding of traditional refractory materials in high-temperature environments.

CN120717775BActive Publication Date: 2025-10-31JIANGSU YONGJIN METAL TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511240714.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-02
Publication Date
2025-10-31
Estimated Expiration
2045-09-02

AI Technical Summary

Technical Problem

Traditional refractory materials have poor thermal shock resistance and insufficient high-temperature strength in high-temperature environments. Furthermore, the weak bonding between polycrystalline alumina fibers and the matrix interface leads to a decrease in the material's high-temperature stability and thermal shock resistance.

Method used

A refractory material was prepared by uniformly mixing polycrystalline alumina fibers with a composite binder, adding corundum, nano-alumina, lanthanum oxide, and silicon carbide, and then sintering it at a programmed temperature. Modified polysiloxane and aluminum dihydrogen phosphate were used to form a continuous composite skeleton to improve the interfacial bonding strength and high-temperature stability.

Benefits of technology

It improves the high-temperature strength and stability of refractory materials, reduces crack formation, and enhances the structural and chemical stability of materials in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention relates to the field of refractory materials technology, and discloses a refractory material based on polycrystalline alumina fiber and its preparation method; including the following steps: Step 1: Mix polycrystalline alumina fiber with a composite binder uniformly, add corundum, nano-alumina, lanthanum oxide and silicon carbide and mix uniformly to obtain a premix; Step 2: Press the premix into a billet under 35~45MPa, dry it at 100~120℃, and then sinter it by programmed temperature rise to obtain the refractory material based on polycrystalline alumina fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of refractory materials technology, specifically a refractory material based on polycrystalline alumina fibers and its preparation method. Background Technology

[0002] Refractory materials play an important role in high-temperature environments in metallurgy, chemical industry, energy and other fields. However, traditional refractory materials (such as high-alumina bricks and magnesia-carbon bricks) have problems such as poor thermal shock resistance and insufficient high-temperature strength. Polycrystalline alumina fibers have become an ideal reinforcing phase for high-performance refractory materials due to their high melting point, low thermal conductivity and excellent thermal shock resistance. However, when inorganic binders (such as phosphates and silica sols) are used alone, the interfacial bonding between the fiber and the matrix is ​​weak, and cracks are easily generated at high temperatures, which leads to a decrease in the high-temperature stability and thermal shock resistance of the material.

[0003] In recent years, organic-inorganic hybrid binders have shown great application potential due to their combination of the flexibility of the organic phase and the high-temperature stability of the inorganic phase. In addition, problems such as uneven fiber dispersion and inaccurate sintering temperature control in traditional processes have also restricted the performance of materials in terms of strength, thermal shock resistance, and corrosion resistance. Therefore, it is of great significance to develop a refractory material based on polycrystalline alumina fiber. Summary of the Invention

[0004] The purpose of this invention is to provide a refractory material based on polycrystalline alumina fiber and its preparation method, so as to solve the problems raised in the prior art.

[0005] To achieve the above objectives, the present invention provides the following technical solution:

[0006] A method for preparing a refractory material based on polycrystalline alumina fibers includes the following steps:

[0007] Step 1: Mix polycrystalline alumina fibers and composite binder evenly, then add corundum, nano alumina, lanthanum oxide and silicon carbide and mix evenly to obtain a pre-mixed material;

[0008] Step 2: Press the pre-mixed material into a billet at 35~45MPa, dry it at 100~120℃, and then sinter it by programmed temperature rise to obtain a refractory material based on polycrystalline alumina fiber.

[0009] In a more optimized form, the raw materials of the premixed material include the following components: by mass parts, 40-50 parts corundum, 13-18 parts polycrystalline alumina fiber, 10-12 parts nano alumina, 3-6 parts lanthanum oxide, 5-7 parts silicon carbide, and 6-10 parts composite binder.

[0010] The preparation method of polycrystalline alumina fiber in the scheme is as follows: aluminum powder is added in batches to an aqueous solution of crystalline aluminum chloride at 85°C to obtain a mother liquor; the mother liquor and silica sol are mixed uniformly at a mass ratio of 92:8, PEG (polyethylene glycol 4000, the amount added is 4wt% of the mother liquor and silica sol) is added, and the mixture is distilled under reduced pressure to obtain a spun colloid with a viscosity of 32 Pa·s; the temperature is controlled at 80°C and the spinning disc speed is 6000 r / min to obtain a fiber preform; the preform is kept at 550°C for 30 minutes, heated to 700°C and kept at 700°C for 40 minutes, and then heated to 1300°C and kept at 1 hour.

[0011] A more optimized method for preparing the composite binder is as follows: (1) Modified polyborosiloxane is added to N,N-dimethylformamide and mixed evenly to obtain a modified polyborosiloxane solution; (2) zirconium propoxide is mixed evenly with ethanol for 30-40 minutes, acetylacetone is added and stirred for 20-25 minutes, diethanolamine is added and stirred for 1-2 hours, the modified polyborosiloxane solution is added, and the mixture is aged at 60-65°C for 6-8 hours to obtain a modified zirconium oxide sol; the modified zirconium oxide sol is ultrasonically dispersed in an ethanol aqueous solution, aluminum dihydrogen phosphate-aqueous solution is added and mixed evenly, and the mixture is stirred at 60-65°C for 1-2 hours, and then allowed to stand at room temperature to mature to obtain the composite binder.

[0012] In a more optimized form, the raw materials for the modified zirconia sol include the following components: by mass parts, 10-15 parts zirconium propoxide, 2-4 parts acetylacetone, 2-4 parts diethanolamine, and 8-12 parts modified polyborosiloxane solution; the mass ratio of aluminum dihydrogen phosphate to the modified zirconia sol is 1:(2-3); and the content of the modified polyborosiloxane solution is 40-50 wt%.

[0013] A more optimized method for preparing modified polyborosiloxane is as follows: (1) Methacryloxysilane-modified nano-zinc oxide is ultrasonically dispersed in N,N-dimethylformamide, hydroquinone monomethacrylate and initiator BPO are added and mixed evenly. Under nitrogen protection, the mixture is heated to 70~80℃ and stirred for 4~7 hours. After removing the solvent, it is added to N,N-dimethylformamide and Soxhlet extracted for 12~18 hours. After drying, phenol-based polymer-modified nano-zinc oxide is obtained; (2) Phenol-based polymer-modified nano-zinc oxide is ultrasonically dispersed in N,N-dimethylformamide and Soxhlet extracted for 12~18 hours. The sound is dispersed in N,N-dimethylformamide to obtain a phenol-based polymer-modified nano-zinc oxide solution, which is set aside. Boric acid and phenyltrimethoxysilane are added to diethylene glycol dimethyl ether and stirred evenly. Nitrogen gas is introduced and stirred at 90-95°C for 1-2 hours. The temperature is raised to 110-115°C and stirred for another 1-2 hours. The temperature is raised to 150-155°C and stirred for 1-1.5 hours. The phenol-based polymer-modified nano-zinc oxide solution and SnCl2 are added and stirred for 5-6 hours. The solvent is removed to obtain modified polyborosiloxane.

[0014] In a more optimized form, the raw material for the phenol-based polymer-modified nano-zinc oxide comprises the following components: by mass parts, 1-1.3 parts of methacryloyloxysilane-modified nano-zinc oxide, 3-5 parts of hydroquinone monomethacrylate, and 0.17-0.2 parts of initiator BPO; the raw material for the modified polyborosiloxane comprises the following components: by mass parts, 2-3 parts of boric acid, 8-10 parts of phenyltrimethoxysilane, 0.8-2 parts of phenol-based polymer-modified nano-zinc oxide, 15-20 parts of diethylene glycol dimethyl ether, and 15-20 parts of N,N-dimethylformamide.

[0015] In the proposed method, nano-zinc oxide is subjected to ultrasonic acid treatment for 5 minutes before modification.

[0016] A more optimized process is as follows: under an air atmosphere, heat to 500-600℃ at a rate of 1-2℃ / min and hold for 1-2 hours; introduce nitrogen at a rate of 10-15L / min; heat to 1000-1200℃ at a rate of 3-5℃ and hold for 1-1.5 hours; continue heating to 1500-1600℃ and hold for 4-5 hours; then cool to room temperature.

[0017] Compared with the prior art, the beneficial effects of the present invention are:

[0018] In this scheme, polycrystalline alumina fibers are uniformly mixed with a composite binder, and corundum, nano-alumina, lanthanum oxide, and silicon carbide are added and uniformly mixed. The mixture is then pressed into a billet, dried, and sintered at a programmed temperature to obtain a refractory material based on polycrystalline alumina fibers.

[0019] Among them, polycrystalline alumina fibers are not easily melted or decomposed at high temperatures, maintaining structural stability in refractory materials and preventing material failure due to collapse at high temperatures; corundum can form the main skeleton of the material, exhibiting good chemical stability and strength at high temperatures; nano-alumina can fill the tiny pores between corundum particles, reducing the porosity of the material and increasing its density. Nano-alumina has a large specific surface area and high surface energy, promoting grain boundary fusion and inhibiting excessive corundum grain growth during sintering, maintaining the fine-grained structure of the material, thus contributing to improved strength and high-temperature stability of refractory materials; at high temperatures, lanthanum oxide (La)... 3+ It will accumulate at the grain boundaries of corundum or alumina, forming low-melting-point La-Al-O compounds, which hinder grain growth, avoid structural inhomogeneity caused by excessively large local grains, suppress the phase transformation of alumina at high temperatures, reduce structural cracking caused by phase transformation, and thus improve the performance of refractory materials; silicon carbide will form a silicon dioxide oxide film at high temperatures, preventing further internal oxidation; at the same time, it can react with alumina to generate an Al2O3-SiC composite phase, which improves the high-temperature strength of refractory materials.

[0020] However, the thermal expansion of polycrystalline alumina fibers differs from that of common refractory matrices, which can induce microcracks during sintering and thus reduce performance. To address this issue, the proposed solution involves preparing a multifunctional composite binder. The polycrystalline alumina fibers and the binder are then thoroughly mixed to improve the interfacial bonding between the fibers and other raw materials, reduce crack formation, and enhance the stability of the refractory material in high-temperature environments.

[0021] In this scheme, zirconium propoxide is used as the zirconium source and diethanolamine is used as the chelating agent. The Zr-OH generated by the hydrolysis of zirconium propoxide condenses with the Si-OH of polyborosiloxane to form an organic-inorganic hybrid network, thus obtaining modified zirconium oxide sol. It is then uniformly mixed with aluminum dihydrogen phosphate under certain conditions to form a uniform colloidal network, which improves the subsequent bonding strength and thus enhances the high-temperature stability of the refractory material.

[0022] To enhance the effect of composite binders on refractory materials, the following method is employed: Hydroquinone monomethacrylate is copolymerized with methacryloxysilane to modify nano-zinc oxide, introducing phenol onto the nano-zinc oxide to obtain phenol-based polymer-modified nano-zinc oxide. Boric acid is first introduced onto the polysiloxane, reacting with the phenolic hydroxyl groups on the phenol-based polymer-modified nano-zinc oxide to obtain modified polyborosiloxane. The modified polyborosiloxane decomposes at high temperature, with Si-O-Si chains forming silicon dioxide and BO bonds forming boron oxide. These two bonds combine to form a high-temperature resistant borosilicate glass phase. The zinc oxide is uniformly... Uniformly dispersed within a borosilicate network, it enhances grain boundary bonding at high temperatures and lowers the melting point of borosilicate glass. It fills pores in refractory materials, improving sintering densification and thus enhancing the high-temperature strength of the refractory. Modified polyborosilicate molecular chains form a physical adsorption layer on the surface of zirconia particles, preventing particle agglomeration through steric hindrance and maintaining the stability and dispersibility of the sol. At high temperatures, the borosilicate glass phase (from modified polyborosilicate) and the aluminum phosphate ceramic phase (from aluminum dihydrogen phosphate) intertwine to form a continuous composite skeleton, endowing the refractory with excellent high-temperature strength and chemical stability. Detailed Implementation

[0023] In the following detailed embodiments, "parts" refers to parts by weight. The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] In this embodiment, it should be noted that there are no special restrictions on the manufacturers of the raw materials involved in this invention. Exemplary examples include: γ-methacryloyloxypropyltrimethoxysilane (CAS number 2530-85-0); zirconium propoxide (CAS number 23519-77-9); acetylacetone (CAS number 123-54-6); diethanolamine (CAS number 111-42-2); hydroquinone monomethacrylate (CAS number 31480-93-0); aluminum dihydrogen phosphate (CAS number 13530-50-2); phenyltrimethoxysilane (CAS number 2996-92-1); nano zinc oxide (product number AM-ZnO-022, particle size 20nm); boric acid (CAS number 10043-35-3); diethylene glycol dimethyl ether (CAS number 111-96-6); and initiator BPO (benzoyl peroxide) (CAS number 94-36-0).

[0025] The preparation method of methacryloyloxysilane modified nano zinc oxide is as follows: 0.7 parts of γ-methacryloyloxypropyltrimethoxysilane are added to a toluene aqueous solution (toluene accounts for 80 wt% in the toluene aqueous solution) and mixed evenly for 30 minutes. Then, 2 parts of nano zinc oxide are added and mixed evenly. The mixture is heated and refluxed for 5 hours. After filtration, washing and drying, methacryloyloxysilane modified nano zinc oxide is obtained.

[0026] Example 1: A method for preparing a refractory material based on polycrystalline alumina fiber, comprising the following steps:

[0027] Pre-preparation: The preparation method of modified polyborosiloxane is as follows: (1) 1.2 parts of methacryloyloxysilane modified nano zinc oxide is ultrasonically dispersed in N,N-dimethylformamide, 3.4 parts of hydroquinone monomethacrylate and 0.2 parts of initiator BPO are added and mixed evenly. Under nitrogen protection, the temperature is raised to 75°C and stirred for 5 hours. After removing the solvent, it is added to N,N-dimethylformamide and Soxhlet extracted for 16 hours. After drying, phenol-based polymer modified nano zinc oxide is obtained; (2) 1 part of phenol-based polymer modified nano zinc oxide is added to N,N-dimethylformamide and Soxhlet extracted for 16 hours. Zinc oxide was ultrasonically dispersed in 15 parts of N,N-dimethylformamide to obtain a phenol-based polymer-modified nano-zinc oxide solution for later use. 2 parts of boric acid and 8 parts of phenyltrimethoxysilane were added to 15 parts of diethylene glycol dimethyl ether and stirred until homogeneous. Nitrogen gas was introduced, and the mixture was stirred at 90°C for 1.5 hours. The temperature was then raised to 110°C and stirred for another hour. The temperature was then raised to 150°C and stirred for 1.5 hours. The phenol-based polymer-modified nano-zinc oxide solution and 0.3 parts of SnCl2 were added, and the mixture was stirred for 5 hours. The solvent was removed to obtain modified polyborosiloxane.

[0028] The preparation method of the composite binder is as follows: (1) Modified polyborosiloxane is added to N,N-dimethylformamide and mixed evenly to obtain a modified polyborosiloxane solution (the solid content is 40wt%); (2) 10 parts of n-propoxide zirconium and 40 parts of ethanol are mixed evenly for 30 minutes, 3 parts of acetylacetone are added and stirred for 20 minutes, 3 parts of diethanolamine are added and stirred for 1 hour, 8 parts of modified polyborosiloxane solution are added and aged at 60°C for 6 hours to obtain modified zirconium oxide sol; the modified zirconium oxide sol is ultrasonically dispersed in an ethanol aqueous solution (ethanol aqueous solution, ethanol accounts for 50wt%), aluminum dihydrogen phosphate-aqueous solution is added and mixed evenly, stirred at 62°C for 1.5 hours, and allowed to stand and mature at room temperature to obtain the composite binder; the mass ratio of aluminum dihydrogen phosphate to modified zirconium oxide sol is 1:2;

[0029] Step 1: Mix 15 parts of polycrystalline alumina fiber with 6 parts of composite binder evenly, add 40 parts of corundum, 10 parts of nano alumina, 4 parts of lanthanum oxide and 5 parts of silicon carbide and mix evenly to obtain a premixed material.

[0030] Step 2: Press the premixed material into a billet at 40MPa, then dry it at 110℃, and then sinter it by programmed temperature rise to obtain a refractory material based on polycrystalline alumina fiber;

[0031] The process conditions for programmed temperature rise are as follows: under an air atmosphere, the temperature is increased to 600℃ at a rate of 1℃ / min and held for 1.5 hours, nitrogen is introduced at a rate of 15L / min, the temperature is increased to 1200℃ at a rate of 3℃ and held for 1 hour, the temperature is further increased to 1600℃ and held for 5 hours, and then cooled to room temperature.

[0032] Example 2; A method for preparing a refractory material based on polycrystalline alumina fiber, comprising the following steps:

[0033] Pre-preparation: The preparation method of modified polyborosiloxane is as follows: (1) 1.2 parts of methacryloyloxysilane modified nano zinc oxide is ultrasonically dispersed in N,N-dimethylformamide, 3.4 parts of hydroquinone monomethacrylate and 0.2 parts of initiator BPO are added and mixed evenly. Under nitrogen protection, the temperature is raised to 75°C and stirred for 5 hours. After removing the solvent, it is added to N,N-dimethylformamide and Soxhlet extracted for 16 hours. After drying, phenol-based polymer modified nano zinc oxide is obtained; (2) 1 part of phenol-based polymer modified nano zinc oxide is added to N,N-dimethylformamide and Soxhlet extracted for 16 hours. Zinc oxide was ultrasonically dispersed in 15 parts of N,N-dimethylformamide to obtain a phenol-based polymer-modified nano-zinc oxide solution for later use. 2 parts of boric acid and 8 parts of phenyltrimethoxysilane were added to 15 parts of diethylene glycol dimethyl ether and stirred until homogeneous. Nitrogen gas was introduced, and the mixture was stirred at 90°C for 1.5 hours. The temperature was then raised to 110°C and stirred for another hour. The temperature was then raised to 150°C and stirred for 1.5 hours. The phenol-based polymer-modified nano-zinc oxide solution and 0.3 parts of SnCl2 were added, and the mixture was stirred for 5 hours. The solvent was removed to obtain modified polyborosiloxane.

[0034] The preparation method of the composite binder is as follows: (1) Modified polyborosiloxane is added to N,N-dimethylformamide and mixed evenly to obtain a modified polyborosiloxane solution (the solid content is 40wt%); (2) 10 parts of n-propoxide zirconium and 40 parts of ethanol are mixed evenly for 30 minutes, 3 parts of acetylacetone are added and stirred for 20 minutes, 3 parts of diethanolamine are added and stirred for 1 hour, 8 parts of modified polyborosiloxane solution are added and aged at 60°C for 6 hours to obtain modified zirconium oxide sol; the modified zirconium oxide sol is ultrasonically dispersed in an ethanol aqueous solution (ethanol aqueous solution, ethanol accounts for 50wt%), aluminum dihydrogen phosphate-aqueous solution is added and mixed evenly, stirred at 62°C for 1.5 hours, and allowed to stand and mature at room temperature to obtain the composite binder; the mass ratio of aluminum dihydrogen phosphate to modified zirconium oxide sol is 1:2;

[0035] Step 1: Mix 18 parts of polycrystalline alumina fiber with 8 parts of composite binder evenly, add 50 parts of corundum, 12 parts of nano alumina, 6 parts of lanthanum oxide and 5 parts of silicon carbide and mix evenly to obtain a premixed material.

[0036] Step 2: Press the premixed material into a billet at 40MPa, then dry it at 110℃, and then sinter it by programmed temperature rise to obtain a refractory material based on polycrystalline alumina fiber;

[0037] The process conditions for programmed temperature rise are as follows: under an air atmosphere, the temperature is increased to 600℃ at a rate of 1℃ / min and held for 1.5 hours, nitrogen is introduced at a rate of 15L / min, the temperature is increased to 1200℃ at a rate of 3℃ and held for 1 hour, the temperature is further increased to 1600℃ and held for 5 hours, and then cooled to room temperature.

[0038] Example 3; A method for preparing a refractory material based on polycrystalline alumina fiber, comprising the following steps:

[0039] Pre-preparation: The preparation method of modified polyborosiloxane is as follows: (1) 1.2 parts of methacryloyloxysilane modified nano zinc oxide is ultrasonically dispersed in N,N-dimethylformamide, 3.4 parts of hydroquinone monomethacrylate and 0.2 parts of initiator BPO are added and mixed evenly. Under nitrogen protection, the temperature is raised to 75°C and stirred for 5 hours. After removing the solvent, it is added to N,N-dimethylformamide and Soxhlet extracted for 16 hours. After drying, phenol-based polymer modified nano zinc oxide is obtained; (2) 1 part of phenol-based polymer modified nano zinc oxide is added to N,N-dimethylformamide and Soxhlet extracted for 16 hours. Zinc oxide was ultrasonically dispersed in 15 parts of N,N-dimethylformamide to obtain a phenol-based polymer-modified nano-zinc oxide solution for later use. 2 parts of boric acid and 8 parts of phenyltrimethoxysilane were added to 15 parts of diethylene glycol dimethyl ether and stirred until homogeneous. Nitrogen gas was introduced, and the mixture was stirred at 90°C for 1.5 hours. The temperature was then raised to 110°C and stirred for another hour. The temperature was then raised to 150°C and stirred for 1.5 hours. The phenol-based polymer-modified nano-zinc oxide solution and 0.3 parts of SnCl2 were added, and the mixture was stirred for 5 hours. The solvent was removed to obtain modified polyborosiloxane.

[0040] The preparation method of the composite binder is as follows: (1) Modified polyborosiloxane is added to N,N-dimethylformamide and mixed evenly to obtain a modified polyborosiloxane solution (the solid content is 40wt%); (2) 10 parts of n-propoxide zirconium and 40 parts of ethanol are mixed evenly for 30 minutes, 3 parts of acetylacetone are added and stirred for 20 minutes, 3 parts of diethanolamine are added and stirred for 1 hour, 8 parts of modified polyborosiloxane solution are added and aged at 60°C for 6 hours to obtain modified zirconium oxide sol; the modified zirconium oxide sol is ultrasonically dispersed in an ethanol aqueous solution (ethanol aqueous solution, ethanol accounts for 50wt%), aluminum dihydrogen phosphate-aqueous solution is added and mixed evenly, stirred at 62°C for 1.5 hours, and allowed to stand and mature at room temperature to obtain the composite binder; the mass ratio of aluminum dihydrogen phosphate to modified zirconium oxide sol is 1:2;

[0041] Step 1: Mix 18 parts of polycrystalline alumina fiber with 6 parts of composite binder evenly, add 45 parts of corundum, 10 parts of nano alumina, 6 parts of lanthanum oxide and 5 parts of silicon carbide and mix evenly to obtain a premixed material.

[0042] Step 2: Press the premixed material into a billet at 40MPa, then dry it at 110℃, and then sinter it by programmed temperature rise to obtain a refractory material based on polycrystalline alumina fiber;

[0043] The process conditions for programmed temperature rise are as follows: under an air atmosphere, the temperature is increased to 600℃ at a rate of 1℃ / min and held for 1.5 hours, nitrogen is introduced at a rate of 15L / min, the temperature is increased to 1200℃ at a rate of 3℃ and held for 1 hour, the temperature is further increased to 1600℃ and held for 5 hours, and then cooled to room temperature.

[0044] Comparative Example 1 is based on Example 2, except that the modified polyborosiloxane is replaced with yttrium nitrate, and the other steps are the same;

[0045] Pre-preparation: The composite binder was prepared by uniformly mixing 10 parts of zirconium propoxide and 40 parts of ethanol for 30 minutes, adding 3 parts of acetylacetone and stirring for 20 minutes, adding 3 parts of diethanolamine and continuing to stir for 1 hour, adding 1.6 parts of yttrium nitrate, and aging at 60°C for 6 hours to obtain modified zirconium oxide sol; the modified zirconium oxide sol was ultrasonically dispersed in an ethanol aqueous solution (ethanol aqueous solution, ethanol accounts for 50 wt%), aluminum dihydrogen phosphate was added and uniformly mixed, stirred at 62°C for 1.5 hours, and allowed to stand at room temperature to mature to obtain the composite binder; the mass ratio of aluminum dihydrogen phosphate to modified zirconium oxide sol was 1:2;

[0046] Step 1: Mix 18 parts of polycrystalline alumina fiber with 8 parts of composite binder evenly, add 50 parts of corundum, 12 parts of nano alumina, 6 parts of lanthanum oxide and 5 parts of silicon carbide and mix evenly to obtain a premixed material.

[0047] Step 2: Press the premixed material into a billet at 40MPa, then dry it at 110℃, and then sinter it by programmed temperature rise to obtain a refractory material based on polycrystalline alumina fiber;

[0048] The process conditions for programmed temperature rise are as follows: under an air atmosphere, the temperature is increased to 600℃ at a rate of 1℃ / min and held for 1.5 hours, nitrogen is introduced at a rate of 15L / min, the temperature is increased to 1200℃ at a rate of 3℃ and held for 1 hour, the temperature is further increased to 1600℃ and held for 5 hours, and then cooled to room temperature.

[0049] Comparative Example 2 is based on Example 2, but without the introduction of phenol-based polymer-modified nano-zinc oxide, and the remaining steps are the same;

[0050] Pre-preparation: The modified polyborosiloxane is prepared by adding 2 parts boric acid and 8 parts phenyltrimethoxysilane to 25 parts diethylene glycol dimethyl ether and stirring until homogeneous. Nitrogen gas is introduced and the mixture is stirred at 90°C for 1.5 hours. The temperature is then raised to 110°C and stirred for another hour. The temperature is then raised to 150°C and stirred for another 1.5 hours. 1 part hydroquinone and 0.3 parts SnCl2 are added and the mixture is stirred for 5 hours. The solvent is then removed to obtain the modified polyborosiloxane.

[0051] The preparation method of the composite binder is as follows: (1) Modified polyborosiloxane is added to N,N-dimethylformamide and mixed evenly to obtain a modified polyborosiloxane solution (the solid content is 40wt%); (2) 10 parts of n-propoxide zirconium and 40 parts of ethanol are mixed evenly for 30 minutes, 3 parts of acetylacetone are added and stirred for 20 minutes, 3 parts of diethanolamine are added and stirred for 1 hour, 8 parts of modified polyborosiloxane solution are added and aged at 60°C for 6 hours to obtain modified zirconium oxide sol; the modified zirconium oxide sol is ultrasonically dispersed in an ethanol aqueous solution (ethanol aqueous solution, ethanol accounts for 50wt%), aluminum dihydrogen phosphate-aqueous solution is added and mixed evenly, stirred at 62°C for 1.5 hours, and allowed to stand and mature at room temperature to obtain the composite binder; the mass ratio of aluminum dihydrogen phosphate to modified zirconium oxide sol is 1:2;

[0052] Step 1: Mix 18 parts of polycrystalline alumina fiber with 8 parts of composite binder evenly, add 50 parts of corundum, 12 parts of nano alumina, 6 parts of lanthanum oxide and 5 parts of silicon carbide and mix evenly to obtain a premixed material.

[0053] Step 2: Press the premixed material into a billet at 40MPa, then dry it at 110℃, and then sinter it by programmed temperature rise to obtain a refractory material based on polycrystalline alumina fiber;

[0054] The process conditions for programmed temperature rise are as follows: under an air atmosphere, the temperature is increased to 600℃ at a rate of 1℃ / min and held for 1.5 hours, nitrogen is introduced at a rate of 15L / min, the temperature is increased to 1200℃ at a rate of 3℃ and held for 1 hour, the temperature is further increased to 1600℃ and held for 5 hours, and then cooled to room temperature.

[0055] Comparative Example 3 is based on Example 2, but with an increased amount of aluminum dihydrogen phosphate added, while the other steps are the same;

[0056] Pre-preparation: The preparation method of the composite binder is as follows: (1) Modified polyborosiloxane is added to N,N-dimethylformamide and mixed evenly to obtain a modified polyborosiloxane solution (the solid content is 40wt%); (2) 10 parts of n-propoxide zirconium and 40 parts of ethanol are mixed evenly for 30 minutes, 3 parts of acetylacetone are added and stirred for 20 minutes, 3 parts of diethanolamine are added and stirred for 1 hour, 8 parts of modified polyborosiloxane solution are added and aged at 60°C for 6 hours to obtain modified zirconium oxide sol; the modified zirconium oxide sol is ultrasonically dispersed in an ethanol aqueous solution (ethanol aqueous solution, ethanol accounts for 50wt%), aluminum dihydrogen phosphate-aqueous solution is added and mixed evenly, stirred at 62°C for 1.5 hours, and allowed to stand and mature at room temperature to obtain the composite binder; the mass ratio of aluminum dihydrogen phosphate to modified zirconium oxide sol is 3.5:1;

[0057] Step 1: Mix 18 parts of polycrystalline alumina fiber with 8 parts of composite binder evenly, add 50 parts of corundum, 12 parts of nano alumina, 6 parts of lanthanum oxide and 5 parts of silicon carbide and mix evenly to obtain a premixed material.

[0058] Step 2: Press the premixed material into a billet at 40MPa, then dry it at 110℃, and then sinter it by programmed temperature rise to obtain a refractory material based on polycrystalline alumina fiber;

[0059] The process conditions for programmed temperature rise are as follows: under an air atmosphere, the temperature is increased to 600℃ at a rate of 1℃ / min and held for 1.5 hours, nitrogen is introduced at a rate of 15L / min, the temperature is increased to 1200℃ at a rate of 3℃ and held for 1 hour, the temperature is further increased to 1600℃ and held for 5 hours, and then cooled to room temperature.

[0060] Testing: The high-temperature flexural strength (MPa) of Examples 1-3 and Comparative Examples 1-3 at 1100℃ was tested; Examples 1-3 and Comparative Examples 1-3 were heated at 1100℃ for 30 minutes, then cooled in water, and the flexural strength (MPa) after 7 cycles was tested; Examples 1-3 and Comparative Examples 1-3 were corroded in a H2-H2O mixed gas at 900℃ for 10 hours, and the flexural strength was tested.

[0061] Table 1

[0062]

[0063] Conclusions: Comparative Example 1 is based on Example 2, but the modified polyborosiloxane is replaced with yttrium nitrate. Because yttrium nitrate cannot replace the interfacial reinforcement effect of polyborosiloxane, the bonding force is reduced, thus leading to a decrease in the performance of Comparative Example 1. Comparative Example 2 is based on Example 2, but without the introduction of phenol-based polymer-modified nano-zinc oxide. The lack of phenol-based polymer-modified nano-zinc oxide results in a weaker high-temperature framework, thus leading to a decrease in the performance of Comparative Example 2. Comparative Example 3 is based on Example 2, but with an increased amount of aluminum dihydrogen phosphate. Excessive aluminum dihydrogen phosphate leads to an increase in the brittle glass phase, thus leading to a decrease in the performance of Comparative Example 3.

[0064] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

Claims

1. A method for preparing a refractory material based on polycrystalline alumina fibers, characterized in that: The following steps are included: Step 1: Mix polycrystalline alumina fibers and composite binder evenly, then add corundum, nano alumina, lanthanum oxide and silicon carbide and mix evenly to obtain a pre-mixed material; Step 2: Press the pre-mixed material into a billet at 35~45MPa, dry it at 100~120℃, and then sinter it by programmed temperature rise to obtain a refractory material based on polycrystalline alumina fiber. The preparation method of the composite binder is as follows: (1) Modified polyborosiloxane is added to N,N-dimethylformamide and mixed evenly to obtain a modified polyborosiloxane solution; (2) zirconium propoxide and ethanol are mixed evenly for 30-40 minutes, acetylacetone is added and stirred for 20-25 minutes, diethanolamine is added, stirring is continued for 1-2 hours, the modified polyborosiloxane solution is added, and the mixture is aged at 60-65°C for 6-8 hours to obtain modified zirconium oxide sol; Modified zirconia sol was ultrasonically dispersed in an ethanol aqueous solution, and aluminum dihydrogen phosphate-aqueous solution was added and mixed evenly. The mixture was stirred at 60-65℃ for 1-2 hours and allowed to stand and mature at room temperature to obtain a composite binder. The preparation method of modified polyborosiloxane is as follows: (1) Methacryloxysilane-modified nano zinc oxide is ultrasonically dispersed in N,N-dimethylformamide, hydroquinone monomethacrylate and initiator BPO are added and mixed evenly. Under nitrogen protection, the temperature is raised to 70~80℃ and stirred for 4~7 hours. After removing the solvent, it is added to N,N-dimethylformamide and Soxhlet extracted for 12~18 hours. After drying, phenol-based polymer-modified nano zinc oxide is obtained; (2) Phenol-based polymer-modified nano zinc oxide is ultrasonically dispersed. A phenol-based polymer-modified nano-zinc oxide solution was obtained in N,N-dimethylformamide and set aside. Boric acid and phenyltrimethoxysilane were added to diethylene glycol dimethyl ether and stirred until homogeneous. Nitrogen gas was introduced and the mixture was stirred at 90-95°C for 1-2 hours. The temperature was then raised to 110-115°C and stirred for another 1-2 hours. The temperature was then raised to 150-155°C and stirred for 1-1.5 hours. The phenol-based polymer-modified nano-zinc oxide solution and SnCl2 were added and stirred for 5-6 hours. The solvent was removed to obtain modified polyborosiloxane. The process conditions for the programmed temperature rise are as follows: under an air atmosphere, heat to 500-600℃ at a rate of 1-2℃ / min and hold for 1-2 hours; introduce nitrogen at a rate of 10-15L / min; heat to 1000-1200℃ at a rate of 3-5℃ and hold for 1-1.5 hours; continue heating to 1500-1600℃ and hold for 4-5 hours; then cool to room temperature.

2. The method for preparing a refractory material based on polycrystalline alumina fiber according to claim 1, characterized in that: The raw materials of the premixed material include the following components: by mass, 40-50 parts corundum, 13-18 parts polycrystalline alumina fiber, 10-12 parts nano alumina, 3-6 parts lanthanum oxide, 5-7 parts silicon carbide, and 6-10 parts composite binder.

3. The method for preparing a refractory material based on polycrystalline alumina fiber according to claim 1, characterized in that: The modified zirconia sol comprises the following components by mass: 10-15 parts zirconium propoxide, 2-4 parts acetylacetone, 2-4 parts diethanolamine, and 8-12 parts modified polyborosiloxane solution; the mass ratio of aluminum dihydrogen phosphate to modified zirconia sol is 1:(2-3); and the content of the modified polyborosiloxane solution is 40-50 wt%.

4. The method for preparing a refractory material based on polycrystalline alumina fiber according to claim 1, characterized in that: The raw materials for the phenol-based polymer-modified nano zinc oxide include the following components: by mass, 1-1.3 parts of methacryloyloxysilane-modified nano zinc oxide, 3-5 parts of hydroquinone monomethacrylate, and 0.17-0.2 parts of initiator BPO; the raw materials for the modified polyborosiloxane include the following components: by mass, 2-3 parts of boric acid, 8-10 parts of phenyltrimethoxysilane, 0.8-2 parts of phenol-based polymer-modified nano zinc oxide, 15-20 parts of diethylene glycol dimethyl ether, and 15-20 parts of N,N-dimethylformamide.

5. A refractory material based on polycrystalline alumina fiber is prepared according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Energy-absorbing material and preparation method thereof

    CN115710425A

  • Heat-resistant coating, heat-resistant insulated wire and heat-resistant film

    JP1995090225A